Comparative genomics of type 1 IncC plasmids from China. (December 2017) - Ma, Lizhi; Yin, Zhe; Zhang, Defu; Zhan, Zhe; Wang, Qian; Duan, Xiongbo; Gao, Huixia; Liang, Quanhui; Zhao, Yuzong; Feng, Jiao; Zhao, Yachao; Tong, Yigang; et al.
Aim: This study dealt with genomic characterization of type 1 IncC resistance plasmids, capable of spreading across taxonomic borders, from China.Materials & methods: p112298-tetA was sequenced and compared with type 1 IncC reference plasmid pR148 and two available sequenced type 1 IncC plasmids pHS36-NDM and pVAS3-1 from China.Results: These plasmids contained one or more exogenous resistance islands, which included the ARI-A islands, the ARI-B islands, the IS Ecp1 -blaCMY units and the bla KPC-2 region and were inserted at various sites in the IncC backbone and thus represented three distinct lineages.Conclusion: Complex rearrangement and homologous recombination events have occurred during evolution of p112298-tetA, making it significantly differ modularly from the other three plasmids with respect to both plasmid backbone and exogenous resistance regions.